(5p-3)(4-p)(8p+1)=0

Simple and best practice solution for (5p-3)(4-p)(8p+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5p-3)(4-p)(8p+1)=0 equation:


Simplifying
(5p + -3)(4 + -1p)(8p + 1) = 0

Reorder the terms:
(-3 + 5p)(4 + -1p)(8p + 1) = 0

Reorder the terms:
(-3 + 5p)(4 + -1p)(1 + 8p) = 0

Multiply (-3 + 5p) * (4 + -1p)
(-3(4 + -1p) + 5p * (4 + -1p))(1 + 8p) = 0
((4 * -3 + -1p * -3) + 5p * (4 + -1p))(1 + 8p) = 0
((-12 + 3p) + 5p * (4 + -1p))(1 + 8p) = 0
(-12 + 3p + (4 * 5p + -1p * 5p))(1 + 8p) = 0
(-12 + 3p + (20p + -5p2))(1 + 8p) = 0

Combine like terms: 3p + 20p = 23p
(-12 + 23p + -5p2)(1 + 8p) = 0

Multiply (-12 + 23p + -5p2) * (1 + 8p)
(-12(1 + 8p) + 23p * (1 + 8p) + -5p2 * (1 + 8p)) = 0
((1 * -12 + 8p * -12) + 23p * (1 + 8p) + -5p2 * (1 + 8p)) = 0
((-12 + -96p) + 23p * (1 + 8p) + -5p2 * (1 + 8p)) = 0
(-12 + -96p + (1 * 23p + 8p * 23p) + -5p2 * (1 + 8p)) = 0
(-12 + -96p + (23p + 184p2) + -5p2 * (1 + 8p)) = 0
(-12 + -96p + 23p + 184p2 + (1 * -5p2 + 8p * -5p2)) = 0
(-12 + -96p + 23p + 184p2 + (-5p2 + -40p3)) = 0

Combine like terms: -96p + 23p = -73p
(-12 + -73p + 184p2 + -5p2 + -40p3) = 0

Combine like terms: 184p2 + -5p2 = 179p2
(-12 + -73p + 179p2 + -40p3) = 0

Solving
-12 + -73p + 179p2 + -40p3 = 0

Solving for variable 'p'.

The solution to this equation could not be determined.

See similar equations:

| 7x+12+6x+13x-16=360 | | 5x^2-20=3x^2-60 | | a^2+4b^2= | | =-2(m+1) | | -12-15-b=1(b+48) | | y=2.5x+4.25 | | 3(x-4)=66*11 | | ?d=5 | | 5z-z+3= | | 4x+159=2x+153 | | 35-17=3x-6 | | -8-12=20 | | 18+3x-x^2=0 | | 33x-9=90 | | (-2w)(2w-3)(3w+10)=0 | | 4x^2-33x+48=-4x+3 | | 3(5c-3)-2=13c+1 | | 4x(2x+y)= | | 6x+21=90 | | 4x+17=-17 | | 8x^2+2n-15=0 | | m(4-m)(5+m)=0 | | y=12.8x+24 | | 11b+7=50 | | 16-x=16x+10 | | -6+[x-4]=-6 | | -5(x+4)=50 | | (4u-3)(u+1)=0 | | 4x^5-12x^4=0 | | 12x+12=x+7 | | 3x-36-180=x | | 12+56=6(t+12) |

Equations solver categories